Dana Pihak Ketiga, Rasio Kecukupan Modal, Pembiyaan Bermasalah, Dan Tingkat Pengembalian Investasi Pada Pembiayaan UMKM - Oki Irawan; Jafril Khalil; Riawan Amin (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2016)
This study aims to determine the effect of third party funds, capital adequacy ratio, problem financing, and return on investment on MSME financing with case studies at Bank Muamalat, Bank Syariah Mandiri and Bank Syariah Mega. This study uses multiple linear regression analysis. The results of this study indicate that the independent variables (the amount of third party funds, capital adequacy ratio, non perfoming financing, return on assets) as a whole contribute or contribute to the dependent variable (financing of SMEs) of 73.6% and the remaining 26.4% of other variables Not included and examined in the equation.